Determination of frequency dependencies of deciles of the signal-to-noise ratio - E. M. Grinev; V. P. Pashintsev; Yu. I. Galushko (Современная наука и инновации)
The level of signal and interference in the decameter range of radio waves is subject to significant random changes, which affects the reliability of radio communications. The reliability of radio communication in the decameter range is determined by the ratio of the average signal level to the noise level at the receiver input to its permissible value, which, in turn, depends on the selected operating frequency. Also an important indicator is the standard deviation (standard deviation) of the signal-tonoise ratio at the receiver input. The latter is considered to be a constant value and is 14 dB. Nevertheless, according to experimental data, the standard deviation (RMS deviation) of the ratio of signal power to noise power at the receiver input in the decameter range may vary depending on frequency, which may affect the accuracy of communication reliability calculations.